Dermoscopy in the diagnosis of juvenile xanthogranuloma - Thaís Erance de Oliveira; Roberto Gomes Tarlé; Lismary Aparecida de Forville Mesquita (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Juvenile xanthogranuloma is the most common form of non-Langerhans cell histiocytosis. It manifests clinically as a red-yellow papule, usually showing spontaneous remission. The diagnosis is based on clinical and histological findings. We report the use of dermoscopy ("setting sun" pattern) as an adjuvant tool in the diagnosis of juvenile xanthogranuloma in a female patient presenting with a 2-month history of a pre-auricular papule.